ANALISIS KESALAHAN BERBAHASA PEMBACA BERITA â€œKALBAR DALAM BERITAâ€ STASIUN TVRI KALIMANTAN BARAT - Febriana, Evva; Heryana, Nanang; Muzammil, Ahmad Rabiul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThis research is motivated by the important of information submission by news listeners as a result of listening to the news. Researcher observed the error reading of news by the newsreader in â€œKalbar dalam Beritaâ€ program station TVRI West Kalimantan period February 2016. This study has a focus on the study of mistake differentiation, pronunciation, and intonation contained in the process of reading the news. The method used is descriptive research with the form of qualitative. The object of this research is newsreader in